Reclaiming Food Security: Assessing Abandoned Spaces as Potential Urban Farms in Lower-Income Kuala Lumpur - Ariffin, A. R. M; Rahman, N. Q. Abd (MAJ - Malaysia Architectural Journal, 2025)
Food insecurity is an alarming issue in most countries with rapid growing population around the globe including Malaysia. This has stemmed the stress in providing a safe and adequate amount of food to all strata of society, especially for the lower-income communities. The global COVID-19 has highlighted the value of food security as boundaries remain closed and nations seek long-term solutions to fend for themselves without relying on food imports and distanced supplies. Malaysia with a total population of 34 million as of 2023, faces tension in the agriculture sector. Urban farming is a key element cited by the United Nations in their Sustainable Development Goals 2030 for self-sufficiency, reducing health and economic inequalities, poverty eradication, women’s, and urban marginal social inclusion, as well as greening the city by reclaiming existing abandoned spaces to promote sustainable development. This paper will investigate potential interstitial urban farming spaces in lower-income neighbourhoods in Kuala Lumpur through space syntax studies. Based on the findings of the study, this paper will formulate the synergies of urban farming and abandoned spaces as part of a food system in shaping sustainable development and inclusive communities. The result will be fundamental data for architects or any relevant bodies to find opportunities in converting interstitial spaces into potential urban farms in making a more self-sufficient urban ecosystem.